The Influence of Discipline, Selection, and Organizational Culture on Employee Performance - Meilinda Meilinda; Louis Louis; Jason Jason; Hendra Nazmi (Almana : Jurnal Manajemen dan Bisnis, 2021)
This study's research background aims to determine how much influence discipline, selection, and organizational culture have on employee performance. The object of research was carried out on employees who work at PT United Rope. The population used in this study was 136 employees with a sample of 101 PT United Rope employees who were obtained using a simple random sampling technique using the Slovin formula. Samples were obtained by distributing questionnaires to employees. The independent variables in this study are discipline, selection, organizational culture. The dependent variable in this study is employee performance. The data analysis technique used includes validity test, reliability test, classical assumption test including normality test, multicollinearity test, heteroscedasticity test, data analysis with multiple linear regression, simultaneous test, and partial test. Based on the research results, discipline, selection, and organizational culture have a positive and significant effect on employee performance. The conclusion of this study, variable field, selection, and corporate culture will improve employee performance. Employee performance will increase if employees can be disciplined in carrying out their work. The company can select employees well in occupying a position, and employees who can apply organizational culture properly will have increased performance.